Deferred Tax Accounting for SMEs: Modified Income Statement Approach - Banka, CA. (Dr.) Anand J (Journal of Accounting, 2020)
Purpose: Accounting for income tax under International Financial Reporting Standards ("˜IFRS') is dealt with in IAS 12 Income Taxes. It is often said that users of financial statements do not find information produced in accordance with IAS 12 useful. This is a serious problem because for many businesses tax is one of the largest expenses. In some cases, preparers find the requirements of IAS 12 difficult to apply in practice. Its requirements are said to be unclear, and preparers sometimes question the relevance and understandability of the information that is provided in accordance with the standard. The IFRS for SMEs currently require use of balance sheet approach for accounting of deferred taxes. In India, the Institute of Chartered Accountants of India (ICAI) - the apex standard-setting body in India, is formulating revised accounting standards for SME's in India. This article examines an alternative to the balance sheet approach which is less complicated and easy to implement.<a href="file:///D:/Documents/Finstock%20Consulting/2020/My%20publications/Cari/Articles/Paid/CA.%20(Dr.)%20Anand%20J%20Banka/Deferred%20Tax%20Accounting%20for%20SMEs%20Modified%20Income%20Statement%20Approach.docx#_msocom_1">[Reviewer1] <a href="file:///D:/Documents/Finstock%20Consulting/2020/My%20publications/Cari/Articles/Paid/CA.%20(Dr.)%20Anand%20J%20Banka/Deferred%20Tax%20Accounting%20for%20SMEs%20Modified%20Income%20Statement%20Approach.docx#_msocom_2">[AB2] Methodology: This article proposes a new method i.e. Modified Income Statement Approach. This method is a mix of income statement approach and balance sheet approach, as it requires recognition of deferred taxes using temporary difference approach but calculated using income statement and the other comprehensive income (in effect, Comprehensive income statement). Modified Income Statement Approach requires comparison of tax expense with the underlying related income and expenses so that they are recognized in the same period. In doing so, it also considers income and expenses recognized in the income statement as well as the Other Comprehensive Income. Hence, this approach is more of temporary difference approach but applied by using income statement method. It covers all items of timing differences and most items of temporary differences. The SMEs have less complicated structures and transactions. Also, in many countries, including India, there exists no concept of tax balance sheet. Hence, it would be worthwhile to ease-out the deferred tax accounting for SMEs. The hypothesis is that application of modified income statement approach can result in similar outcome as the balance sheet approach. Findings: A survey of 50 top companies in India was conducted. The results show that 60% of the companies would have recognized the same deferred tax asset/ liability under both the methods i.e. modified income statement approach and balance sheet approach. Balance 40% had some minor differences, but such transactions may be less frequent for SME. On an average, the impact of using modified income approach as against balance sheet approach is a mere 4%. The only items not covered by the modified income statement approach as against the balance sheet approach are Fair valuation of assets/ liabilities on business combination, Compound financial instrument and the existence of undistributed profits of subsidiaries, branches, associates and joint arrangements<a href="file:///D:/Documents/Finstock%20Consulting/2020/My%20publications/Cari/Articles/Paid/CA.%20(Dr.)%20Anand%20J%20Banka/Deferred%20Tax%20Accounting%20for%20SMEs%20Modified%20Income%20Statement%20Approach.docx#_msocom_3">[Reviewer3] .<a href="file:///D:/Documents/Finstock%20Consulting/2020/My%20publications/Cari/Articles/Paid/CA.%20(Dr.)%20Anand%20J%20Banka/Deferred%20Tax%20Accounting%20for%20SMEs%20Modified%20Income%20Statement%20Approach.docx#_msocom_4">[AB4] Unique contribution to theory, practice and policy: <a href="file:///D:/Documents/Finstock%20Consulting/2020/My%20publications/Cari/Articles/Paid/CA.%20(Dr.)%20Anand%20J%20Banka/Deferred%20Tax%20Accounting%20for%20SMEs%20Modified%20Income%20Statement%20Approach.docx#_msocom_5">[Reviewer5] <a href="file:///D:/Documents/Finstock%20Consulting/2020/My%20publications/Cari/Articles/Paid/CA.%20(Dr.)%20Anand%20J%20Banka/Deferred%20Tax%20Accounting%20for%20SMEs%20Modified%20Income%20Statement%20Approach.docx#_msocom_6">[AB6] To balance out the cost and benefits of implementing an accounting standard as per the framework, it is critical that SME's use a simpler and less complicated method which is easy to understand and implement. Modified income statement approach is easy to apply and not complicated or technical to understand. In India, companies are used to calculating deferred tax using income statement approach. Hence, this will be a small change from the existing approach, while achieving the objectives of the balance sheet approach. Hence, modified income statement approach seems to be an appropriate method for SMEs.